Astraeus – VI. Hierarchical assembly of AGN and their large-scale effect during the Epoch of Reionization. Issue 3 (30th November 2022) - Trebitsch, Maxime; Hutter, Anne; Dayal, Pratika; Gottlöber, Stefan; Legrand, Laurent; Yepes, Gustavo
ABSTRACT: In this work, the sixth of a series, we use the seminumerical rAdiative tranSfer coupling of galaxy formaTion and Reionization in N -body dark-matter simUlationS (astraeus ) framework to investigate the nature of the sources that reionized the Universe. We extend astraeus, which already couples a galaxy formation semi-analytical model with a detailed seminumerical reionization scheme, to include a model for black-hole formation, growth, and the production of ionizing radiation from associated active galactic nuclei (AGNs). We calibrate our fiducial AGN model to reproduce the bolometric luminosity function at z ≃ 5, and explore the role of the resulting AGN population in reionizing the Universe. We find that in all the models yielding a reasonable AGN luminosity function, galaxies dominate overwhelmingly the ionizing budget during the Epoch of Reionization, with AGN accounting for 1–10 per cent of the ionizing budget at z = 6 and starting to play a role only below z ≲ 5.